Linguistic and Cultural Problems in Translation and Solutions - Ahmed Azeez Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This study which is entitled "linguistic And Cultural problems in translation and Solutions" is about translation in general and the major linguistic and cultural problems that the translator faces in translating any type of text. Translation is a very ancient and important communicator between languages ​​throughout the history of human beings, until the present time. My study is an attempt to tackle translation problems and it is concerned with translation definition as the translation theorists have defined. An increasing number of people are engaged as professionals in such work, and together with the expansion of university education in most countries, this has resulted in the establishment of a large number of international translators who are training programs of various length and character. The pioneers in this field are Catford, Newmark, Nida and Khulussi. Then it deals with different theories of translation according to the theorists. The study also, closely concentrates on different linguistic problems of translation, namely related to word order, passivation, structure length, idiomatic expressions and concord. It does not cast problems without giving their solutions. Wherever we give a problem, then we provide solutions for it in a pretty clear way. The focus of this study is on the translation process and the performance of the translation task. In this process, as a communicative and language processing event, the starting point is the source text and the individual translator’s comprehension of it, and of the concrete task of translating it.